Study of Color Influence on Shopper Perception Toward Packaged Mineral Water product - Pramuwidyatama, Muchammad Gilang; Hudrasyah, Herry (Journal of Business and Management, 2013)
The shopper are having numerous brands in selecting the packaged drinking water. Packaged drinking water is characterized by an over abundance of product choice and diversity. As a result, shopper are faced with the burden of making product evaluations and purchase decisions with an overwhelming set of informational cues such as packaging design and color. Color provides a unique source of information for picking out an object from its background Besides aiding our ability to detect the presence of objects, color also helps us recognize and distinguish them from other objects in the environment. The research is for analyzing and determining marketing strategy in using color as tool for brand identity, visual communication tools, and create perception towards all generation whose being shopper from packaged mineral water product. Based on the research writer found the following 8 perceptions that influenced by the color of packaging from mineral water products, they are likeliness, attractiveness, quality, visibility, easy to remember, Go Green, perceived value and willingness to buy. This research also find that generational gap influences shopper perceptions towards packaged mineral water product based on the color and color can be used for visual communication tools for building desired perception on packaged mineral water products.Â Key words : Color, Generational Gap, Shopper Perception, Packaged Mineral Water